2002
DOI: 10.1200/jco.2002.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Transcatheter Arterial Chemoembolization as Compared With Hepatic Resection in Hepatocellular Carcinoma Patients With Compensated Liver Function in a Hepatitis B Virus–Endemic Area: A Prospective Cohort Study

Abstract: TACE proved to be as effective as HR in the subpopulations with UICC T3N0M0 or CLIP 1-2 HCC and adequate liver function, and even with UICC T1-2N0M0 HCC when lipiodol was compactly retained in the tumor. In such cases, the choice of treatment modality between TACE and HR may be left to the patient's preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 44 publications
4
74
3
Order By: Relevance
“…Overall, 2037 papers were initially retrieved, of which 3 were included (Eurvilaichit and Kanjanapitak, 2000;Lee et al, 2002;Liu et al, 2007) (Figure 1). Study characteristics were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 2037 papers were initially retrieved, of which 3 were included (Eurvilaichit and Kanjanapitak, 2000;Lee et al, 2002;Liu et al, 2007) (Figure 1). Study characteristics were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In an individual study by Lee et al, the survival benefit of hepatic resection after initial TACE should be attributed to the subgroup of patients at less advanced tumor stages (Lee et al, 2002). The investigators conducted the subgroup analyses according to the International Union Against Cancer (UICC) stage and the Cancer of the Liver Italian Program (CLIP) scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al compared tace with surgical resection in a large study 94 in which 91 patients underwent resection and 91 received multiple sessions of tace. The survival rate was significantly higher with liver resection than with tace (p = 0.0038), median survival time being 66 months and 37 months respectively.…”
Section: Tacementioning
confidence: 99%
“…In particular, transcatheter arterial chemoembolization is widely used to manage unresectable hepatocellular carcinoma. Extrahepatic collateral arteries supply the hepatocellular carcinoma, even when the hepatic artery is patent [14]. This stems largely from the discovery of the involvement of the IPAs in the arterial supply and growth of hepatocellular carcinoma [5,27].…”
mentioning
confidence: 99%